Does Late Maturity Alpha-Amylase Impact Wheat Baking Quality? - Newberry, Marcus; Zwart, Alexander B.; Whan, Alex; Mieog, Jos C.; Sun, May; Leyne, Emmett; Pritchard, Jenifer; Daneri-Castro, Sergio Nicolas; Ibrahim, Kutty; Diepeveen, Dean; Howitt, Crispin A.; Ral, Jean-Philippe F. (Frontiers in Plant Science, 2018)
Late maturity α-amylase (LMA) and Pre Harvest Sprouting (PHS) are both recognized as environmentally induced grain quality defects resulting from abnormally high levels of -amylase. LMA is a more recently identified quality issue that is now receiving increasing attention worldwide and whose prevalence is now seen as impeding the development of superior quality wheat varieties. LMA is a genetic defect present in specific wheat genotypes and is characterized by abnormally elevated levels of the high pI TaAMY1 -amylase, triggered by environmental stress during wheat grain development. TaAMY1 remains present in the aleurone through the harvest, lowering Falling Number (FN) at receival, causing a down-grading of the grain, often to feed grade, thus reducing the farmers’ income. This downgrading is based on the assumption within the grain industry that, as for PHS, a low FN represents poor quality grain. Consequently any wheat line possessing low FN or high alpha-amylase levels is automatically considered a poor bread wheat despite there being no published evidence to date, to show that LMA is detrimental to end product quality. To evaluate the validity of this assumption we undertook a comprehensive evaluation of baking properties from LMA prone lines using a subset of tall non-Rht lines from a Multi-parent Advanced Generation Inter-Cross (MAGIC) wheat population grown at three different sites. LMA levels were determined along with quality parameters including end product functionality such as bread loaf volume and weight, crumb firmness, oven spring, slice area and brightness and gas cell number. No consistent or significant genetic or phenotypic correlation was found between LMA related Falling Number and any of the quality traits. This manuscript provides for the first time, compelling evidence that LMA has limited impact on bread baking end product functionality.